2009
DOI: 10.1111/j.1528-1167.2009.02131.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of levetiracetam and valproate on reproductive endocrine function studied in human ovarian follicular cells

Abstract: SUMMARYPurpose: Recent animal studies have indicated possible reproductive endocrine effects of levetiracetam (LEV). The aim of the present study was to investigate possible reproductive endocrine effects of LEV compared to valproate (VPA) using human ovarian follicular cells. Methods: Cell cultures of human granulosa cells were prepared. First, the effect of the drugs on basal and follicle-stimulating hormone (FSH)-stimulated estradiol secretion was investigated at different concentrations of LEV (12, 20, 50,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 51 publications
3
14
0
2
Order By: Relevance
“…However, VPA completely reversed FSH-induced expression of CYP19A1 and HSD17B1 and partially reversed IGF-induced CYP19A1 and HSD17B1 expression. An inhibitory effect of VPA on CYP19A1 in FSH-treated human GC was also observed by Tauboll et al [38]. As discussed below the enzymes encoded by CYP19A1 and HSD17B1 both play key roles in the synthesis of estradiol-17β by GC.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…However, VPA completely reversed FSH-induced expression of CYP19A1 and HSD17B1 and partially reversed IGF-induced CYP19A1 and HSD17B1 expression. An inhibitory effect of VPA on CYP19A1 in FSH-treated human GC was also observed by Tauboll et al [38]. As discussed below the enzymes encoded by CYP19A1 and HSD17B1 both play key roles in the synthesis of estradiol-17β by GC.…”
Section: Discussionsupporting
confidence: 61%
“…Using GC harvested from women undergoing laparotomy procedures for infertility treatment Tauboll et al [38] recently reported that VPA suppressed basal and FSH-induced estradiol secretion. Similarly, in the porcine TC/GC co-culture study of Tauboll et al [23] VPA reduced basal and FSH-induced estrogen secretion.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, decreased serum FSH, LH, and testosterone levels were observed in our high-dose group. Studies showed that LH and FSH levels were not altered [44, 45], while testosterone levels were increased [4446] in male epileptic patients due to LEV treatment. Epilepsy treatment with LEV in prepubertal children did not cause a meaningful change in hormone levels [47].…”
Section: Discussionmentioning
confidence: 99%
“…A trend towards reduced HRs for breast carcinoma and the absence of ovarian and testicular carcinomas in the exposed group are worth mentioning in view of the effect of valproate on endocrine tissue, which might make hormonal‐responsive tumours more sensitive to the antitumour effects of valproate (30). Although purely speculative, the possibility of an inverse association between valproate use and hormone‐responsive tumours merits further study using a larger sample.…”
Section: Discussionmentioning
confidence: 99%